High levels of self-efficacy in patients with type 2 diabetes attending a tertiary level clinic - K. Mostert Wentzel; C. Nel; A.J. van Rooijen; J. Francis; G. Gibbs; K. Hacker; S. Gebert (AOSIS, 2008)
Self-management is a vital element in the care of type 2diabetes patients.  In turn, self-efficacy plays a major role in patients' self-management. Self-efficacy is the patient's personal judgement of his/herconfidence in performing aspects of diabetes self-management.  This study investigated the level of self-efficacy of patients attending the Pretoria Academic Hospital Diabetes Clinic, in the light of high levels ofre-admission due to complications, suggesting low self-efficacy levels. Eighty type 2 diabetes patients, mean age of 59 years, completed thepublished IDEA LL baseline questionnaire, to establish a self-efficacyscore.  Relationships between self-efficacy and demographic factors wereinvestigated using the chi-square test. The mean self-efficacy level of thesample population is excellent (mean = 85.44%).A lthough self-reported self-efficacy levels are excellent, in comparison to the Sarkar study (2006) in which participants only scored "fair", it is speculated that self-efficacy is not transferred to self-management behaviour in thispopulation.  Afrikaans and English speaking participants score significantly better than those from other language categories. There is a positive relationship between self-efficacy and level of education and employment status (tendedtowards significance with p values of 0.06 and 0.07 respectively). A lthough self-efficacy scores of clients at this tertiary level outpatient clinic are excellent, further research is necessary to quantify self-management strategies andto correlate these with self-efficacy levels.